Perioperative management for people with chronic kidney disease receiving dialysis undergoing major surgery: a protocol for a scoping review - Paul E Ronksley; Matthew James; Janine F Farragher; Brenda R Hemmelgarn; Shannon M Ruzycki; Maoliosa Donald; Tyrone G Harrison; Connor O'Rielly; Deirdre McCaughey; Kelly B Zarnke (BMJ Open)
Introduction People with chronic kidney disease receiving dialysis (CKD G5D) have an increased risk of poor postoperative outcomes and a high incidence of major surgery. Despite the high burden of these combined risks, there is a paucity of evidence to support tailored perioperative strategies to manage this population. A comprehensive evidence synthesis would inform the management of these patients in the perioperative period and identify knowledge gaps. We describe a protocol for a scoping review of the literature to identify existing perioperative strategies, protocols, pathways and interventions for people with CKD G5D undergoing major surgery.Methods and analysis We will conduct a scoping review in accordance with the Joanna Briggs Institute methodology and report per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. In February 2020, we will complete our search of MEDLINE, EMBASE, CINAHL Plus, Cochrane Database of Systematic Reviews, and Cochrane Controlled Trials Registry for published literature from inception to present. All study types are eligible for inclusion, without language restriction. Studies reporting a perioperative intervention in adult patients with CKD G5D are eligible for inclusion. Studies in prevalent kidney transplant patients or patients with acute kidney injury, and studies that report on surgical approaches without consideration of perioperative management strategies, will be excluded. Reviewers will independently assess abstracts for all identified studies in duplicate, and again at the full-text stage. Following published literature searches, a search of the grey literature will be developed. We will extract and narratively report study, participant and intervention details. This will include a summary table outlining the strategies employed, organised into post hoc developed perioperative domains.Ethics and dissemination Ethical considerations do not apply to this scoping review. Findings will be disseminated through relevant conference presentations and publications.